A rede padrão de repouso parece preservada intrinsecamente mas sua conectividade funcional extrínseca pode estar comprometida em usuários de crack-cocaína - Martins, Diego Lima Nava (2016)
Default Mode Network (DMN) seems to be affected in drug addiction. Decreased functional connectivity has been described in psychostimulants users (cocaine, nicotine, and caffeine) and also in addicted to depressant drugs (alcohol, heroin, prescribed opioids) but no study has investigated the DMN functional connectivity in crack-cocaine dependents so far. Here, inpatient crack-cocaine users in abstinence for at least 4 weeks and age-matched non-addicted controls underwent to functional Magnetic Resonance Imaging acquired when they rested with eyes closed (rs-fMRI) in 1.5 T or 3.0 T scanners. After data preprocessing, DMN were defined by spatial independent component analysis (ICA) and seed-based correlation analysis, by chosen regions of interest centered in the ventral Anterior Cingulate Cortex (vACC) and in the Posterior Cingulate Cortex (PCC). Global DMN functional connectivity was not different between crack-cocaine users and age-matched controls in rs-fMRI acquired in both scanners. The seed-based analysis showed greater negativity of the connectivity between vACC and superior parietal lobe when compared to agematched controls (p < 0.0322). No differences between groups were found in the functional connectivity between PCC and other brain regions. Thus, the total DMN functional connectivity searched by ICA was found preserved in crack-cocaine dependents in abstinence. When a seed-based correlation analysis was applied searching for a single metric functional connectivity between specific brain regions, a greater negativity was found between medial frontal region and the posterior brain region, suggesting that although a broad DMN was unaffected a selective functional connectivity may be compromised in crack-cocaine addiction.